Comparative Analysis of Bioactive Phenolic Compounds and Fatty Acids in Seeds and Seedlings of Canadian Alfalfa, Sainfoin, and Fenugreek - Srinivas Sura; Chamali Kodikara; Surya Acharya; Ali Sabra; Champa Wijekoon (Applied Biosciences, 2023)
The interest in under-utilized crops as a functional food for animals and humans has been increasing recently with advancing research and the need for crop improvement. Canadian forage crops including alfalfa (Medicago sativa L.) and fenugreek (Trigonella foenum-graecum L.) are marketed in various forms due to their traditionally known health benefits. Sainfoin (Onobrychis viciifolia Scop.) is another forage crop with potential health benefits containing beneficial nutraceuticals. In this study, we assessed selected bioactive phenolic compounds and fatty acids in seeds and seedlings of Canadian-grown alfalfa, sainfoin, and fenugreek. Various phenolic compounds were detected in all three forage crop seeds and seedlings. In general, Sainfoin seeds were high in phenolic compounds relative to that of alfalfa and fenugreek. Chlorogenic acid, epigallo catechin, and gallic acid were at high concentrations at 56.6, 86.8, and 64.7 µg.g−1, respectively, compared to other phenolic compounds in sainfoin seeds. The fatty acids content (%) was significantly affected by the seedling stage and crop type. Some of the bioactive compounds present in seeds were not detected in seedling stages. The comparative bioactive phenolic compounds and fatty acid assessments of these forage legumes could potentially be used as biomarkers for the selection and development of favorable cultivars for animal and human nutrition. In addition, these crops could be used for isolating these bioactive compounds, and thus increasing their agri-food value.